Pengaruh Jenis Mulsa dan Dosis Mikoriza Arbuskula Terhadap Pertumbuhan Dan Hasil Tanaman Tomat (Lycopersicum esculentum Mill) - Malahayati Malahayati; Boy Riza Juanda; Ainul Mardiyah (Universitas Teuku Umar, 2025)
Tomatoes are plants with a short life cycle, can grow as high as 1 to 2 meters. This plant has green, yellow and red fruits that are usually used as vegetables in cooking or eaten directly without being processed. Tomatoes have stems and leaves that cannot be consumed because they are still in the same family as potatoes and eggplants that contain alkaloids. The problems that arise today are unsuitable climate conditions and less supportive soil conditions. This is because cultivating tomatoes with soil temperatures that are too high can cause excessive evaporation so that the percentage of groundwater loss increases. This will have an impact on the inhibition of the nutrient absorption process. Therefore, it is necessary to make efforts to provide mulch and provide biological fertilizers. The aim of this research was to determine the effect of mulch type and arbuscular mycorrhiza dosage on the growth and yield of tomato plants. This research was carried out in Langsa City using a factorial group random design (RAK), namely the Mulch Type Factor with the notation (M) consisting of 4 levels, namely control, silver black plastic mulch, sugarcane bagasse mulch, rock mulch and Arbuscular Mycorrhiza dosage factor with the notation (F) consists of 4 levels, namely control, 5 gr/plant, 10 gr/plant, 15 gr/plant. The results of the research showed that the influence of the type of mulch had a significant effect on plant height, fruit weight and average fruit weight per plant as well as an interaction between the type of mulch and the dose of plant height and weight per fruit.Keywords: tomato plants, type of mulch, arbuscular mycorrhiza